2022
DOI: 10.1364/ol.457529
|View full text |Cite
|
Sign up to set email alerts
|

Tapered Yb-doped fiber enabled a 4 kW near-single-mode monolithic fiber amplifier

Abstract: In this Letter, we demonstrate a monolithic high-power master oscillator power amplifier by using a home-made double-clad tapered Yb-doped fiber (T-YDF) with an input end of ∼20/400 µm and an output end of ∼30/600 µm. Thanks to perfect core/cladding matching with the fiber components at both ends of the T-YDF, the laser is pumped bidirectionally and an output power of over 4 kW with a high slope efficiency of 84.1% and excellent beam quality M2 ∼ 1.46 is achieved. In contrast to previous work on common fiber l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…With the development of fiber preform preparation and mechanical polishing technology, the studies of tapered fibers has evolved to more degrees of freedom along the longitudinal dimension, which is driven by better pump absorption capacity and greater single-mode potential. A series of representative results at several-kilowatt-level have been reported with near single-mode outputs [76,[258][259][260][261][262][263][264][265][266][267][267][268][269][270][271][272][273][274][275][276][277][278][279][280]. Table 2 summarizes the recent progress of tapered fibers for HPFLs applications.…”
Section: Geometric Structures Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…With the development of fiber preform preparation and mechanical polishing technology, the studies of tapered fibers has evolved to more degrees of freedom along the longitudinal dimension, which is driven by better pump absorption capacity and greater single-mode potential. A series of representative results at several-kilowatt-level have been reported with near single-mode outputs [76,[258][259][260][261][262][263][264][265][266][267][267][268][269][270][271][272][273][274][275][276][277][278][279][280]. Table 2 summarizes the recent progress of tapered fibers for HPFLs applications.…”
Section: Geometric Structures Engineeringmentioning
confidence: 99%
“…For better compatibility with commercial optical fiber devices, fiber with a small end of 20/400 µm and a large end of 30/600 µm was introduced for higher output power [265]. Similar applications in fiber amplifiers also increased the signal power to 2.17 kW [266]; most recently, the output power in long-tapered fiber was pulled to over 4 kW [76].…”
Section: Geometric Structures Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides designing these special transverse structures, modifying and optimizing the optical fiber in the longitudinal is another effective pathway to inhibit nonlinear effects and mode instability simultaneously. As published in the literature [8][9][10][11][12], tapered double-clad fibers (T-DCFs), with a gradually varying core profile diameter along the fiber length, provide many prominent properties, including relatively simple structure, suppression of nonlinear effects and good beam quality maintenance. These unique features make them attracted considerable attention in the power scalability of high power pulse and CW fiber lasers.…”
Section: Introductionmentioning
confidence: 99%
“…For a CW operation, in 2018, our research group demonstrated an all-fiberized longtapered fiber amplifier, yielding an output power of 1.47 kW together with a laser beam quality of M 2 ~1.8 [10]. In 2022, Ye et al promoted the output laser power of the active T-DCF-based fiber amplifier to 4 kW in CW regime [11]. Apart from this, the improved tapered optical fibers have been received more and more attention to meet different high power applications, such as saddle-shaped fiber, spindle-shaped fiber and so on.…”
Section: Introductionmentioning
confidence: 99%